2021
DOI: 10.3390/agronomy11061104
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Agrobacterium Mediated Genetic Transformation in Paspalum scrobiculatum L. (Kodo Millet)

Abstract: An efficient and reproducible protocol for Agrobacterium tumefaciens mediated genetic transformation was developed for kodo millet (Paspalum scrobiculatum L.) by optimizing various parameters. Agrobacterium strains EHA 105 and LBA 4404 harboring plasmids pCNL 56 and pCAMBIA 2300, respectively, provided the highest transformation efficiency. Addition of acetosyringone (AS) in infection medium (200 µM EHA 105, 250 µM–LBA 4404) and co-cultivation medium (50 µM) increased the transformation efficiency. Transient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As a result, ascorbic acid, as a scavenging chemical, significantly enhanced GUS expression in, and shoot regeneration from, infected Chinese cabbage explants. Similarly, Bhatt et al (2021) reported maximum transformation efficiency was recorded in the presence of 2.5 mg/L ascorbic acid along with L-cysteine and silver nitrate in the pretreatment solution of Kodo millet callus.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a result, ascorbic acid, as a scavenging chemical, significantly enhanced GUS expression in, and shoot regeneration from, infected Chinese cabbage explants. Similarly, Bhatt et al (2021) reported maximum transformation efficiency was recorded in the presence of 2.5 mg/L ascorbic acid along with L-cysteine and silver nitrate in the pretreatment solution of Kodo millet callus.…”
Section: Discussionmentioning
confidence: 69%
“…When the antioxidants were used in the growing media, the tissue necrosis and browning can significantly reduce phenolic exudation in infected explants, and thereby increase the regeneration efficiency followed by improving the transformation efficiency. The addition of L-cysteine, ascorbic acid and silver nitrate in co-cultivation medium has also been revealed to considerably recover transformation efficiency in rice ( Enríquez-Obregón et al, 1999 ) and Kodo millet ( Bhatt et al, 2021 ). It has also been confirmed that L-cysteine improves the Agrobacterium -mediated transformation in soybean by reducing oxidative stress ( Olhoft et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequences of teff (VanBuren et al, 2020) and fonio millet were recently completed (Abrouk et al, 2020). In addition, the protocols for genetic transformation with agrobacterium and biolistic approaches in (Vetriventhan et al, 2020;Bhatt et al, 2021). These advances are expected to enhance the prospects of understanding the underlying genomics of small millets.…”
Section: Breeding Objectives and Prospects In Overcoming Constraintsmentioning
confidence: 99%
“…The genome sequences of teff ( VanBuren et al, 2020 ) and fonio millet were recently completed ( Abrouk et al, 2020 ). In addition, the protocols for genetic transformation with agrobacterium and biolistic approaches in finger millet, agrobacterium and biolistic methods in foxtail millet, biolistic methods in barnyard millet, agrobacterium-mediated approaches in teff and fonio, and agrobacterium-mediated methods in Kodo millet are now available ( Vetriventhan et al, 2020 ; Bhatt et al, 2021 ). These advances are expected to enhance the prospects of understanding the underlying genomics of small millets.…”
Section: Progress Of Crop Improvement In Small Milletsmentioning
confidence: 99%
“…After years of experiments, this perspective was completely changed. Numerous species, including cereals [179][180][181][182][183], gymnosperms [184][185][186][187], and algae [188] that were previously recalcitrant to A. tumefaciens infection can now be transformed. A. tumefaciens is not the only bacterium tested for the biological transformation of plants.…”
Section: Biological Systemsmentioning
confidence: 99%